The post-corporate world : life after capitalism - Korten, David C. (Berrett-Koehler, 1999)
"In this book, David Korten makes a compelling and well-documented case that capitalism's claims to being the engine of wealth creation, the champion of democracy, and the embodiment of the market economy are unfounded. Among Korten's conclusions: Capitalism is a pathology that afflicts democracies and market economies in the absence of vigilant public oversight. The consolidation of economic power under a handful of global mega-corporations is a victory for central planning - not the market economy. The alternative to the new global capitalism is a planetary system of democratically governed market economies that honor basic market principles of the sort actually advocated by Adam Smith."--Jacket